Pengaruh Pajak Restoran, Pajak Parkir, Dan Pajak Penerangan Jalan Terhadap Pendapatan Asli Daerah (PAD) Kota Madiun Tahun 2014-2020 - Rizka Putriyanti; Muhammad Imron; Choirum Rindah Istiqaroh (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2023)
This study aims to determine the effect of partially or simultaneously Restaurant Tax, Parking Tax, and Street Lighting Tax on Regional Original Income of Madiun City in 2014-2020. The data used in this study is secondary data that is time series from 2014 to 2020. The data analysis technique uses multiple linear regression analysis techniques, classical assumption test, partial significance test (t test), simultaneous significance test (F test), and test the coefficient of determination with the help of the IBM SPSS Statistics program. The results showed that: (1) Restaurant Tax (X1) partially had no significant effect on Madiun City's Original Regional Income (PAD) in 2014-2020. Restaurant tax t count < t table where 0.129 < 2.776 with a significant 0.906 > 0.05; (2) Parking Tax (X2) partially has no significant effect on Madiun City's Original Regional Revenue (PAD) in 2014-2020. Parking tax t count < t table where 0.266 < 2.776 with a significance of 0.807 > 0.05; (3) Street Lighting Tax partially has a significant effect on Madiun City's Original Regional Revenue (PAD) in 2014- 2020. The value of t-count Street Lighting Tax > t table where 5.783 > 2.776 with a significant 0.010 < 0.05; (4) Restaurant Tax (X1), Parking Tax (X2), Street Lighting Tax (X3) simultaneously have a significant effect on Madiun City's Original Regional Revenue (PAD) in 2014-2020. The calculated F value > F table (41.685 > 5.14) where the significance value is 0.006 < 0.05.